Fatores genéticos e não genéticos relacionados às doses de varfarina e à qualidade da anticoagulação em pacientes cardiopatas - Aline de Oliveira Magalhaes Mourao (2017)
Warfarin is widely used in the prevention of thromboembolic events. The International Normalized Ratio (INR) is the parameter of choice for monitoring the response to warfarin and Time in Therapeutic Range (TTR) is used to assess the quality of anticoagulation. The aim of this study was to (1) evaluate the association of CYP2C9*2 (rs1799853), CYP2C9*3 (rs1075910) and VKORC1-G1639A (rs9923231) and non-genetic factors with low doses of warfarin (<17.5 mg/week) and TTR and (2) to create algorithms for predicting warfarin doses and TTR.A retrospective cohort study that included 312 patients on chronic warfarin use recruited at an anticoagulation clinic (AC) of a Brazilian university hospital. The indications for oral anticoagulation included atrial fibrillation (AF), mechanical heart valve prosthesis or a history of ischemic stroke. Genotypes were determined using real-time Polymerase Chain Reaction (PCR) and TTR was calculated by the Rosendaal method. The association of sociodemographic, clinical, behavioral and pharmacotherapeutic and genetic data with warfarins doses and RNI recorded between 2009-2015 was investigated. For data analysis, multivariate regression and the Construction of the Receiver Operator Characteristic Curve (ROC) were performed.The mean age of the patients was 60.4 (± 13.5) years, 59.9% of them were female sex. Few patients (12.8%) used warfarin weekly doses <17.5mg. In the multivariate regression model, the variables associated with warfarin doses <17.5mg/week were target INR 2.00-3.00 [odds ratio (OR) 3.66, confidence interval (CI) 1.40-11.24; p= 0.013), genotype VKORC1 AA (OR 32,34, CI 11,39-102,91, p<0,001) and genotype CYP2C9 2/2, 2/3 or 3/3 (OR 15,34, IC 2, 99-82.78, p<0.001). The ROC curve presented an area of82.8% (75.4-90.3%) and cutoff point of 0.18 with sensitivity and specificity of 67.5% and 87.5%, respectively. The mean TTR was 63.4%, and 122 (60.9%) patients had good quality of anticoagulation (TTR> 60%) and 64 (20.5%) had an excellent quality of anticoagulation (TTR 75%). In multivariate analysis, the increase in the number of reports of non-adherence to warfarin (OR 1.60, CI 1.11-2.35, p=0.013), the increase in absenteeism in the INR control visits (OR 1.66, CI 1.22-2.30, p=0.002) and the increase in the number of warfarin dose adjustments (OR 2.32, CI 1.87-2.96, p<0.001) increased the chance of patient presented TTR60%.The increase in the duration of follow-up (OR 1.001, CI 1.001-1.002, p<0.001) and target INR between 2.00 and 3.00 (OR 6.097, CI 2.358-17.844, p<0.001) increased the patient's chance of presenting TTR75%; the increase in the number of visits to control the INR (RC 0.742, CI 0.568-0.965, p=0.026), the increase in the number of absenteeism in the INR control visits (OR 0.480, IC 0.285-0.776, p=0.004) and the increase in the number of warfarin dose adjustments (RC 0.319; CI 0.197-0.489; p<0.001) were negatively associated with TTR 75%.These results suggest that sociodemographic, clinical and genetic factors influence the dose variability of warfarin, while sociodemographic, clinical, behavioral and genetic factors modify the quality of anticoagulant therapy.